2018
DOI: 10.7150/thno.21967
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanowire Networks for Dual-Isolation and Detection of Tumor-Associated Circulating Biomarkers

Abstract: Purpose: Recent developments in genomic and molecular methods have revolutionized the range of utilities of tumor-associated circulating biomarkers in both basic and clinical research. Herein, we present a novel approach for ultrasensitive extraction of cfDNA and CTCs, at high yield and purity, via the formation of magnetic nanowire networks.Materials and Methods: We fabricated and characterized biotinylated cationic polyethylenimine and biotinylated antibody cocktail-conjugated magnetic polypyrrole NWs (PEI/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…31,32 Furthermore, the MNWs have shown a high internalization by cells in comparison to other magnetic nanoparticles, such as IONs, improving the enrichment and multiplexing yield. 26,28,33 As a consequence, MNWs have recently attracted attention as enrichment agents for studying breast and lung cancers, 34,35 CTCs, 36 and leukemia. 37 Regardless of the tremendous opportunities for MNWs, they have not been used as self-standing biomarkers for multiplexing applications up to date due to three major drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Furthermore, the MNWs have shown a high internalization by cells in comparison to other magnetic nanoparticles, such as IONs, improving the enrichment and multiplexing yield. 26,28,33 As a consequence, MNWs have recently attracted attention as enrichment agents for studying breast and lung cancers, 34,35 CTCs, 36 and leukemia. 37 Regardless of the tremendous opportunities for MNWs, they have not been used as self-standing biomarkers for multiplexing applications up to date due to three major drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…[36] The integrated nanomaterial enabled the maximal loading of capture agents and magnetic particles for superior capture and purification of cfDNA at 0.01-1000 ng mL −1 . [36] Toralla et al developed an integrated microfluidic magnetic extraction platform (METRO) for cfDNA isolation from biological samples such as undiluted serum. [37] The capture domain of the microfluidic platform was equipped with paramagnetic microparticles which can be expanded by flowing binding buffer (pH < 6) through the channel.…”
Section: Na Preparationmentioning
confidence: 99%
“…Reproduced with permission. [36] Copyright 2018, Ivyspring. manipulation of DNA under an electric field.…”
Section: Na Preparationmentioning
confidence: 99%
“…Recently, we developed a new genotyping assay that accurately and rapidly detects small amounts of tumor-derived cell-free DNA (cfDNA) in various body fluids in patients with lung cancer or cervical cancer. [18][19][20] This assay isolates cfDNA in body fluids using nanowires (NW) and directly detects DNA variants or mutations without PCR amplification within 1 hour. Our previous studies demonstrated that this NW-based cfDNA assay can be used to detect low-abundance DNA variants in plasma cfDNA with high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, due to the vast amount of raw data generated by NGS sequencing and its complexity, the role of bioinformatics experts is crucial for processing, interpreting, and analyzing complex bioinformatics data, ultimately obtaining biological specificity from sequenced samples. Recently, we developed a new genotyping assay that accurately and rapidly detects small amounts of tumor‐derived cell‐free DNA (cfDNA) in various body fluids in patients with lung cancer or cervical cancer [18–20]. This assay isolates cfDNA in body fluids using nanowires (NWs) and directly detects DNA variants or mutations without PCR amplification within 1 hour.…”
Section: Introductionmentioning
confidence: 99%